Equity in mathematics education : influences of feminism and culture - Kaiser, Gabriele; Rogers, Pat (Falmer Press, 1995)
"Research and intervention over the past three decades have greatly increased our understanding of the relationship between gender and participation in mathematics education. Research, most of it quantitative, has taught us that gender differences in mathematics achievement and participation are not due to biology, but to complex interactions among social and cultural factors, societal expectations, personal belief systems and confidence levels. Intervention to alter the impact of these interactions has proved successful, at least in the short term. Typically, interventions sought to remedy perceived 'deficits' in women's attitudes and/or aptitudes in mathematics by means of 'special programmes' and 'experimental treatments'. But recent advances in scholarship regarding the teaching and learning of mathematics have brought new insights. Current research, profoundly influenced by feminist thought and methods of enquiry, has established how a fuller understanding of the nature of mathematics as a discipline, and different, more inclusive instructional practices can remove traditional obstacles that have thwarted the success of women in this important field. Some argue that practices arising out of contemporary analysis will improve the study of mathematics for all students, male and female alike. This book provides teachers, educators and other interested readers with an overview of the most recent developments and changes in the field of gender and mathematics education. Many of the chapters in this volume arose out of sessions."--Jacket